Oxysterol 7-α Hydroxylase (CYP7B1) Attenuates Metabolic-Associated Fatty Liver Disease in Mice at Thermoneutrality - Ioannis Evangelakos; Dorothee Schwinge; Anna Worthmann; Clara John; Niklas Roeder; Paul Pertzborn; Janina Behrens; Christoph Schramm; Ludger Scheja; Joerg Heeren (Cells, 2021)
Ambient temperature is an important determinant of both the alternative bile acid synthesis pathway controlled by oxysterol 7-α hydroxylase (CYP7B1) and the progression of metabolic-associated fatty liver disease (MAFLD). Here, we investigated whether CYP7B1 is involved in the etiology of MAFLD under conditions of low and high energy expenditure. For this, Cyp7b1−/− and wild type (WT) mice were fed a choline-deficient high-fat diet and housed either at 30 °C (thermoneutrality) or at 22 °C (mild cold). To study disease phenotype and underlying mechanisms, plasma and organ samples were analyzed to determine metabolic parameters, immune cell infiltration by immunohistology and flow cytometry, lipid species including hydroxycholesterols, bile acids and structural lipids. In WT and Cyp7b1−/− mice, thermoneutral housing promoted MAFLD, an effect that was more pronounced in CYP7B1-deficient mice. In these mice, we found higher plasma alanine aminotransferase activity, hyperlipidemia, hepatic accumulation of potentially harmful lipid species, aggravated liver fibrosis, increased inflammation and immune cell infiltration. Bile acids and hydroxycholesterols did not correlate with aggravated MAFLD in Cyp7b1−/− mice housed at thermoneutrality. Notably, an up-regulation of lipoprotein receptors was detected at 22 °C but not at 30 °C in livers of Cyp7b1−/− mice, suggesting that accelerated metabolism of lipoproteins carrying lipotoxic molecules counteracts MAFLD progression.